Differences in drug utilisation between men and women: a cross-sectional analysis of all dispensed drugs in Sweden. Issue 5 (3rd May 2013) - Loikas, Desirée; Wettermark, Björn; von Euler, Mia; Bergman, Ulf; Schenck-Gustafsson, Karin
Abstract : Objectives: Ascertain the extent of differences between men and women in dispensed drugs since there is a lack of comprehensive overviews on sex differences in the use of prescription drugs. Design: Cross-sectional population database analysis. Methods: Data on all dispensed drugs in 2010 to the entire Swedish population (9.3 million inhabitants) were obtained from the Swedish Prescribed Drug Register. All pharmacological groups with ambulatory care prescribing accounting for >75% of the total volume in Defined Daily Doses and a prevalence of >1% were included in the analysis. Crude and age-adjusted differences in prevalence and incidence were calculated as risk ratios (RRs) of women/men. Results: In all, 2.8 million men (59%) and 3.6 million women (76%) were dispensed at least one prescribed drug during 2010. Women were dispensed more drugs in all age groups except among children under the age of 10. The largest sex difference in prevalence in absolute numbers was found for antibiotics that were more common in women, 265.5 patients (PAT)/1000 women and 191.3 PAT/1000 men, respectively. This was followed by thyroid therapy (65.7 PAT/1000 women and 13.1 PAT/1000 men) and antidepressants (106.6 PAT/1000 women and 55.4 PAT/1000 men). Age-adjusted relative sex differences in prevalence were found in 48 of the 50 identified pharmacological groups. The pharmacological groups with the largest relative differences of dispensed drugs were systemic antimycotics (RR 6.6 CI 6.4 to 6.7), drugs for osteoporosis (RR 4.9 CI 4.9 to 5.0) and thyroid therapy (RR 4.5 CI 4.4 to 4.5), which were dispensed to women to a higher degree. Antigout agents (RR 0.4 CI 0.4 to 0.4), psychostimulants (RR 0.6 CI 0.6 to 0.6) and ACE inhibitors (RR 0.7 CI 0.7 to 0.7) were dispensed to men to a larger proportion. Conclusions: Substantial differences in the prevalence and incidence of dispensed drugs were found between men and women. Some differences may be rational and desirable and related to differences between the sexes in the incidence or prevalence of disease or by biological differences. Other differences are more difficult to explain on medical grounds and may indicate unequal treatment.